The role of chromatin remodeling complexes in Schwann cell development - Fröb, Franziska; Wegner, Michael (Glia, 2019)
Schwann cells develop from neural crest cells in an ordered series of events and give rise to myelinating and nonmyelinating subtypes. In their mature state, myelinating Schwann cells produce myelin sheaths that provide trophic support to axons and allow saltatory conduction in the vertebrate peripheral nervous system. Each step of Schwann cell development requires defined changes in chromatin structure that are catalyzed by chromatin remodeling complexes. Over the last years, all major types of chromatin remodeling complexes have been detected in Schwann cells and several have been functionally analyzed. SWI/SNF-type, CHD-type, and INO80/SWR-type chromatin remodelers in particular have been shown to interact with multiple cell-type specific transcription factors and histone modifiers and to be important regulators of Schwann cell development. As a result of different recruitment strategies, each chromatin remodeler targets defined genomic areas and impacts unique mechanisms at specific stages of Schwann cell development. Chromatin remodeling complexes undoubtedly constitute essential components of the Schwann cell regulatory network.
CRIS-Team WoS Importer:2019-12-27